2012
DOI: 10.1021/jm3011806
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Selective and Potent Inhibitors of Gram-Positive Bacterial Thymidylate Kinase (TMK)

Abstract: Thymidylate kinase (TMK) is an essential enzyme in bacterial DNA synthesis. The deoxythymidine monophosphate (dTMP) substrate binding pocket was targeted in a rational-design, structure-supported effort, yielding a unique series of antibacterial agents showing a novel, induced-fit binding mode. Lead optimization, aided by X-ray crystallography, led to picomolar inhibitors of both Streptococcus pneumoniae and Staphylococcus aureus TMK. MICs < 1 μg/mL were achieved against methicillin-resistant S. aureus (MRSA),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 20 publications
1
61
0
Order By: Relevance
“…3). The screen identified known inhibitors of DNA metabolism that were present in the compound library, such as quinolones (9) and other inhibitors of DNA gyrase (GyrA) (39), as well as ATPase inhibitors of GyrB (40)(41)(42)(43), DNA ligase (44,45), and thymidylate kinase (46,47). Given that the assay identified a wide variety of inhibitors, rather than inhibitors of just a single target, the assay was validated as a useful probe to identify inhibitors of DNA metabolism (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3). The screen identified known inhibitors of DNA metabolism that were present in the compound library, such as quinolones (9) and other inhibitors of DNA gyrase (GyrA) (39), as well as ATPase inhibitors of GyrB (40)(41)(42)(43), DNA ligase (44,45), and thymidylate kinase (46,47). Given that the assay identified a wide variety of inhibitors, rather than inhibitors of just a single target, the assay was validated as a useful probe to identify inhibitors of DNA metabolism (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We found that Martínez-Botella et al (2012, 2013 reported that piperidinylthymines inhibit gram-positive bacterial Tmk. Martínez-Botella et al (2012) also reported the positions of the Tmk piperidinylthymine binding site.…”
Section: Literature Search For Lead Inhibitor Compoundsmentioning
confidence: 87%
“…We found that Martínez-Botella et al (2012, 2013 reported that piperidinylthymines inhibit gram-positive bacterial Tmk. Martínez-Botella et al (2012) also reported the positions of the Tmk piperidinylthymine binding site. Furthermore, we found that Keating et al (2012) reported that piperidinylthymines exhibited activity in an in vivo mouse model of S. aureus MRSA252 infection and that Martínez-Botella et al (2013) reported that piperidinylthymines are moderately and weakly active against gramnegative and human Tmk, respectively.…”
Section: Literature Search For Lead Inhibitor Compoundsmentioning
confidence: 87%
See 1 more Smart Citation
“…In case of prokaryotic TMKs various compounds such as modified thymine base, 3 substituted nucleosides and nucleotides, 2 ,3 bicyclic analogues, thymidine 5 -O-monophosphate analogues, substituted benzyl thymine analogues and acyclic nucleoside analogues were tested against Mycobacterium tuberculosis Vanheusden et al, 2002Vanheusden et al, , 2003Vanheusden et al, 2004;Van Daele et al, 2006;Gasse et al, 2007;Familiar et al, 2008). Piperidinylthymine analogues were found to be active against Staphylococcus aureus TMK and a commercially available compound 1-methyl-6-phenyl imidazopyrinon and its derivatives inhibited Pseudomonas aeruginosa TMK at nanomolar concentration (Martinez-Botella et al, 2012;Choi et al, 2012). Recently TMPK has been validated as a drug target in gram-positive bacterium Staphylococcus aureus (Keating et al, 2012).…”
Section: Introductionmentioning
confidence: 99%